Complete Proton Transfer Cycle in GFP and Its T203V and S205V Mutants1. Issue 32 (18th June 2015) - Laptenok, Sergey P.; Lukacs, Andras; Gil, Agnieszka; Brust, Richard; Sazanovich, Igor V.; Greetham, Gregory M.; Tonge, Peter J.; Meech, Stephen R.
Abstract Proton transfer is critical in many important biochemical reactions. The unique three‐step excited‐state proton transfer in avGFP allows observations of protein proton transport in real‐time. In this work we exploit femtosecond to microsecond transient IR spectroscopy to record, in D2O, the complete proton transfer photocycle of avGFP, and two mutants (T203V and S205V) which modify the structure of the proton wire. Striking differences and similarities are observed among the three mutants yielding novel information on proton transfer mechanism, rates, isotope effects, H‐bond strength and proton wire stability. These data provide a detailed picture of the dynamics of long‐range proton transfer in a protein against which calculations may be compared.